(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2023)
Background:The hospitality industry is recovering, evolving, and adapting itself in the post COVID-19 era through innovative and sustainable practices backed by the use of technology in entire hotel operations. The hotel Front Office department is no exception in utilizing these evolved practices to understand and influence the customer behaviour while exploring all possible measures to enhance the overall guest stay experience in the post- COVIDtimes. The Front Office department plays a vital role in the passage of accurate and timely information required for flawless guest management in the hotels. Throughout the COVID-19 period, the Front Office practices have evolved through different stages depending upon the factors such as guest preferences, safety and security measures, hygienic conditions, sustainability and use of technology. Objectives: The major objectives are to study the post COVID-19 Hotel guest preferences of non-star category hotels with respect to changing scenario in the Hospitality Industry, to analyse the gaps between hotel guest expectations and perceptions in service quality with special mention of the front office department and to highlight the future challenges faced by hotel industry and suggest possible measured to overcome these challenges. Methodology: Hybrid research approach has been adopted in this study. Grounded theory in qualitative research approach with interview and semi-structured questionnaires are the data collection tools. Survey method with structured questionnaire are quantitative data collection tools. Collected data were analysed through content and thematic tools for qualitative data and quantitative data were analysed through descriptive statistics (Mean, SD, percentage) and paired t-test as an inferential statistical tool has been applied in this study for conclusion purpose. Results: Result indicates negative as Expected value – perceived value = - (negative). Conclusion: It is concluded that hotel-guests’ are not satisfied as provided facilities are not as per guests’ expectation. This study gives overview of guests’ expectation. It helps hoteliers for modification of hotel’s facilities for the guest. The limitation of the study is that the study is conducted in NCR only. Hotels of the same category in the other cities/town may be conducted for getting actual scenario of the phenomena of the hotels. In addition, the study proposes that hotels should adjust their room and service pricing to reflect the reduced demand during the COVID era. Furthermore, the hotel industry will face ongoing challenges, and hotels must be adaptable to remain competitive. By embracing new technologies, providing distinctive experiences, and implementing sustainable practices, hotels can overcome these challenges and flourish in the years ahead.